I understand the intuition behind the question but I'm trying to prove it to myself with math.


1 Answer 1


Since $\mathbb{E}(\varepsilon \mid X) = 0$, the law of iterated expectation gives $\mathbb{E}(\varepsilon) = \mathbb{E}(\mathbb{E}(\varepsilon \mid X)) = \mathbb{E}(0) = 0$. This reduces the covariance equation to:

$$\begin{equation} \begin{aligned} \mathbb{Cov}(\varepsilon, X) = \mathbb{E}(\varepsilon X) - \mathbb{E}(X) \mathbb{E}(\varepsilon) = \mathbb{E}(\varepsilon X). \\[6pt] \end{aligned} \end{equation}$$

Now we use the law of iterated expectation again to get:

$$\begin{equation} \begin{aligned} \mathbb{Cov}(\varepsilon, X) &= \mathbb{E}(\varepsilon X) \\[6pt] &= \mathbb{E}(\mathbb{E}(\varepsilon X \mid X)) \\[6pt] &= \mathbb{E}(X \cdot \mathbb{E}(\varepsilon \mid X)) \\[6pt] &= \mathbb{E}(X \cdot 0) \\[6pt] &= \mathbb{E}(0) = 0. \\[6pt] \end{aligned} \end{equation}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.